Formulation and Evaluation of Trovafloxacin: The Next Generation of Fluoroquinolones as Sustained Release Tablet - Singh, Asheesh; Singh, Vinayaditya; Singh, Jagrati; Sharma, Naveen (Current Research in Pharmaceutical Sciences, 2014)
Trovafloxacin is a synthetic chemotherapeutic antibiotic of the fluoroquinolone drug class and is used to treat severe or life-threatening bacterial infections or bacterial infections that have failed to respond to other antibiotic classes. It is sold under various brand names, such as Trovan and Tavanic, the most common. Trovafloxacin is considered to be same as Ofloxacin by the U.S. Food and Drug Administration (FDA), with the exception of the potency shown in vitro against mycobacteria. In vitro, it is, in general, twice as potent as ofloxacin, whereas d-ofloxacin is less active against mycobacteria. The advantage of administering a single dose of a drug that is released over an extended period of time instead of numerous doses is now a day’s area of interest for formulation scientists in Pharmaceutical industry. There are several advantages of sustained release drug delivery over conventional dosage forms like improved patient compliance due to less frequent drug administration, maximum utilization of the drug, increased safety margin of potent drug, reduction of fluctuation in steady-state drug levels, reduction in healthcare costs through improved therapy and shorter treatment period. Wide varieties of polymers like Hydroxy Propyl Methyl Cellulose (HPMC), Carboxy Methyl Cellulose (CMC), Ethyl Cellulose (EC), Cellulose Acetate Phthalate, HPMC K100M, Xanthan gum, Carrageenan gum, Karaya gum, HPMC K15, Carbopol 971P and Carbopol 974P etc. are available for retarding the release rate of drugs hence sustains the action of drugs.